Upaya Peningkatan UMKM melalui Sosialisasi Pemanfaatan Teknologi Digital Bagi Pelaku Usaha di Kampung Tanjung Kuras, Kecamatan Sungai Apit, Kabupaten Siak - Pane, Rico Purnawandi; Subekti, Muhamad Nelwan Wahyuda; Dullah, Amin; Habib, Bayu Darma; Damanik, Sandi; Rinaldi, Rinaldi; Nisa, Larasita Iffatun; Rahmadani, Fitri Nova; Kurnia, Victoria Gebby; Adelia, Vida; Shabrina, Shabrina; Azzura, Nadia (Abdimas Indonesian Journal, 2025)
The development of information technology is inevitable, and has expanded to various aspects of our lives, one of which is the economic aspect in Indonesia. The economy is an aspect that needs to be considered in this all-digital era in order to continue to be able to grow and develop so that it can compete globally. One of the economic supporters in Indonesia is MSMEs. Therefore, MSME actors must be able to adapt and take advantage of information technology developments to improve their business fields. So it is necessary to hold Socialization of the use of digital technology for business actors in an effort to increase MSMEs in Tanjung Kuras Village, Sungai Apit District, Siak Regency. This devotion is carried out with the aim of improving MSMEs by providing insight and understanding to MSME actors so that they can be more independent, able to compete, able to take advantage of opportunities, able to take advantage of existing potential, able to innovate, wide market reach, facilitate transactions, and licensing/legality. The method used in this service activity is Participatory Rural Apraical (PRA). PRA is one of the methods in community empowerment that involves community participation. The result of this service is an increase in knowledge and skills and MSME actors who do not have business licenses, logos and banners now have them.